Are All Endoscopy-Related Musculoskeletal Injuries Created Equal? Results of a National Gender-Based Survey. (28th March 2021) - Pawa, Swati; Banerjee, Promila; Kothari, Shivangi; D'Souza, Sharlene L.; Martindale, Sarah L.; Gaidos, Jill K. J.; Oxentenko, Amy S.; Burke, Carol A.
Abstract : INTRODUCTION: Endoscopy-related injury (ERI) is common in gastroenterologists (GI). The study aim was to assess the prevalence of self-reported ERI, patterns of injury, and endoscopist knowledge of preventative strategies in a nationally representative sample. METHODS: A 38-item electronic survey was sent to 15, 868 American College of Gastroenterology physician members. The survey was completed by 1, 698 members and was included in analyses. Descriptive, univariate, and multivariate analyses were conducted to evaluate the likelihood of ERI based on workload parameters and gender. RESULTS: ERI was reported by 75% of respondents. ERI was most common in the thumb (63.3%), neck (59%), hand/finger (56.5%), lower back (52.6%), shoulder (47%), and wrist (45%). There was no significant difference in the prevalence of ERI between men and women GI. However, women GI were significantly more likely to report upper extremity ERI while men were more likely to report lower-back pain-related ERI. Significant gender differences were noted in the reported mechanisms attributed to ERI. Most respondents did not discuss ergonomic strategies in their current practice (63%). ERI was less likely to be reported in GI who took breaks during endoscopy ( P = 0.002). DISCUSSION: ERI is highly prevalent in GI physicians. Significant gender differences regarding specific sites affected by ERI and the contributing mechanisms were observed. Results strongly support institution of training in ergonomics for all GI as a strategy to prevent its impact on providers of endoscopy.